Cytogenetic and molecular characterization of a recombinant X chromosome in a family with a severe neurologic phenotype and macular degeneration - Magini, Pamela (Mol Cytogenet, 2015)
BACKGROUND: Duplications of MECP2 gene in males cause a syndrome characterized by distinctive clinical features, including severe to profound mental retardation, infantile hypotonia, mild dysmorphic features, poor speech development, autistic features, seizures, progressive spasticity and recurrent infections. Patients with complex chromosome rearrangements, leading to Xq28 duplication, share most of the clinical features of individuals with tandem duplications, in particular neurologic problems, suggesting a major pathogenetic role of MECP2 overexpression. RESULTS: We performed cytogenetic and molecular cytogenetic studies in a previously described family with affected males showing congenital ataxia, late-onset progressive myoclonic encephalopathy and selective macular degeneration. Microsatellite, FISH and array-CGH analyses identified a recombinant X chromosome with a deletion of the PAR1 region, encompassing SHOX, replaced by a duplicated segment of the Xq28 terminal portion, including MECP2. CONCLUSIONS: Our report describes the identification of the actual genetic cause underlying a severe syndrome that previous preliminary analyses erroneously associated to a terminal Xp22.33 region. In the present family as well as in previously reported patients with similar rearrangements, the observed neurologic phenotype is ascribable to MECP2 duplication, with an undefined contribution of the other involved genes. Maculopathy, presented by affected males reported here, could be a novel clinical feature associated to Xq28 disomy due to recombinant X chromosomes, but at present the underlying pathogenetic mechanism is unknown and this potential clinical correlation should be confirmed through the collection of additional patients.